Bioinformatic analyses of metallome and structural analysis of sirtuin from Glaciozyma antarctica PII2 - Foong, Pik Mun (2014)
Metal ions are essential elements that are extensively involved in many cellular activities. With rapid advancements in genome sequencing techniques, bioinformatic approaches have provided a promising way to extract the functional information of a protein directly from its primary structure. Recent studies have suggested that the metal content of an organism can be predicted from its genome sequences using bioinformatic approaches, and the variation of cellular metal contents is found to correlate with the bioavailability of metal ions in the adjacent environment. The focus of this study is targeted towards the analysis of metal composition of a psychrophilic yeast Glaciozyma antarctica PI12 isolated from sea ice of Antarctica. Since the cellular metal content of an organism is usually reflected in the expressed metal-binding proteins, the putative metal-binding sequences from G. antarctica PI12 were identified in respect to their sequence homologies, domain compositions, protein families and cellular distribution. The homologous metal-related sequences from G. antarctica PI12 were identified by BLAST using annotated queries available in the public database. Metal-binding protein domains in the sequences were also inspected to enhance the accuracy of prediction. Proteins with novel metal-binding sites were identified using SVMProt. All putative metalbinding proteins were assigned with Gene Ontology (GO) terms and predicted subcellular location for functional inferences. Most of the approaches have suggested that the metallome of G. antarctica PI12 was enriched in zinc, and descending in the order of Zn > Mg > Ca, Fe > Cu, Mn > Na, K, Co, Ni. Upon comparison, the metal composition of G. antarctica PI12 was found to be almost identical with those of its warm-counterparts. However, distinctive variations were noticed when compared with bacteria. The observations suggested that G. antarctica PI12 could have inherited a conserved trend of metal usage similar to modern eukaryotes that enriched in zinc. Subsequently, sirtuin, a zinc-bound NAD+-dependent deacetylase was selected for further structural investigation. A predicted model was obtained through comparative modeling and its quality was evaluated. To investigate the role of zinc, the model and its apo (with zinc removed) were independently subjected to 10 ns molecular dynamics (MD) simulations coupled at temperature 277 K, 285 K and 303 K. The results suggested that zinc may function to retain the native conformation of sirtuin and prevent it from denaturing. It was also noticed that the structural flexibility of the protein was improved by altering its amino acid composition and enhancing solvent accessibility at certain regions. In conclusion, the metal content of G. antarctica PI12 was depicted through an integration of multiple bioinformatic approaches and its strategy in coldadaptation can be inferred from the structural variation and dynamics studies of sirtuin.